(3ecGJHI fUQ GHf aJhMs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hUd cJGH GdTjN GdaGVd CWGd Gddg HbGg hCeG eG PcQJg ef LgI ZjQc eef jYfG HgPG GdMGd s
(3BNQgG (B:s
(3hbO hgH eG ajgG ef GdGdI heG JHbG ajgG def jbhi Ydi eWGdHJge hdG jXdege hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis